INVESTIGATING ONLINE GAME ADDICTION: AN IN-DEPTH ANALYSIS OF DESIGN ELEMENTS THROUGH THE PLAYER ENGAGEMENT MODEL - Sachu, Berlin; S, Kadeswaran; R, Jayseelan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study investigates game addiction by using the design elements of Online video games through the player engagement model, The study explores the motive of the addicted behaviour of gamers and finding the association between game addiction and game design elements standardised by game creators. The study utilizes a quantitative methodology, and gathered data from 309 samples through questionnaires focusing on their engagement with game design elements and Game addiction was assessed using the Video Game Addiction Test. Statistical analyses reveal associations among variables, indicating that the design elements of online video games do not directly contribute to the development of video game addiction. Instead, it is evident that individuals with lower levels of addiction place a significant emphasis on video game design aspects such as immersion, game mechanics, motivation, and social interaction. The research suggests that understanding the impact of design elements on addiction in gaming contexts can inform gamers about how to mitigate game addiction.